2012
DOI: 10.1186/1471-2164-13-643
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and metabolomic analysis of Ascophyllum nodosum mediated freezing tolerance in Arabidopsis thaliana

Abstract: BackgroundWe have previously shown that lipophilic components (LPC) of the brown seaweed Ascophyllum nodosum (ANE) improved freezing tolerance in Arabidopsis thaliana. However, the mechanism(s) of this induced freezing stress tolerance is largely unknown. Here, we investigated LPC induced changes in the transcriptome and metabolome of A. thaliana undergoing freezing stress.ResultsGene expression studies revealed that the accumulation of proline was mediated by an increase in the expression of the proline synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(85 citation statements)
references
References 81 publications
(98 reference statements)
0
85
0
Order By: Relevance
“…In the literature some studies report that after the application of biostimulants expression of genes related to defense mechanism is upregulated. The treatment of A. thaliana plants exposed to freezing stresses with algae extract result in changes of expression in about 5% (1113) of all A. thaliana genes (Nair et al, 2012). About 2% (463 genes) of the differentially expressed genes are upregulated and 3% (650 genes) downregulated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature some studies report that after the application of biostimulants expression of genes related to defense mechanism is upregulated. The treatment of A. thaliana plants exposed to freezing stresses with algae extract result in changes of expression in about 5% (1113) of all A. thaliana genes (Nair et al, 2012). About 2% (463 genes) of the differentially expressed genes are upregulated and 3% (650 genes) downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…About 2% (463 genes) of the differentially expressed genes are upregulated and 3% (650 genes) downregulated. The authors report that some of these genes were involved in the plant's defense mechanisms (Nair et al, 2012). The application of algal extracts prior to pathogen infection in alfalfa cause upregulation of 152 genes, mostly plant defense genes, such as those involved in phytoalexin, PR proteins, cell wall proteins, and oxylipin pathways (Cluzet et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…showed that extracts of A. nodosum and its lipophilic fraction increased tolerance of Arabidopsis to freezing temperatures and that this was associated with protection of membrane integrity, reduced expression of chlorophyllase genes, and increased expression of three cold tolerance genes. (Nair et al 2012) determined that the lipophilic components (LPC) of the seaweed extract increased proline content in Arabidopsis plants undergoing freezing stress and that this increase was associated with increased expression of proline synthesis genes. In addition, the concentration of total soluble sugars in the cytosol and the proportion of unsaturated fatty acids increased in LPC-treated plants under freezing stress.…”
Section: Plant Metabolism and Physiologymentioning
confidence: 99%
“…Their modes of action are not yet well understood, but the application of new analytical and molecular tools is providing new insight into their effects on gene expression, biochemical pathways, and physiological processes Nair et al 2012;Jannin et al 2013;Wally et al 2013). Greater understanding of the modes of action of this renewable resource will be helpful in optimizing its use in the sustainable management of agricultural and horticultural systems (Khan et al 2009;Quilty and Cattle 2011).…”
Section: Concluding Remarks For Seaweed Extractsmentioning
confidence: 99%
“…The lipophilic components were found to be rich in fatty acids such as butyric acid, palmitic acid, oleic acid, linoleic acid the sterol fucosterol. These extracts increased proline content and total soluble sugars, contributing to freezing tolerance [56]. A. nodosum extracts have even been used to reduce cold stress sensitivity in Kappaphycus alvarezii.…”
Section: Algal Extractsmentioning
confidence: 99%